Mutode :generic javascript and node.js mutation testing tool (2018)
Mutation testing is a technique in which faults (mutants) are injected into a program or application to assess its test suite effectiveness. It works by inserting mutants and running the applications test suite to identify if the mutants are detected (killed) or not (survived) by the tests. Although computationally expensive, it has proven to be an effective method to assess application test suites. Several mutation testing frameworks and tools have been built for the various programing languages, however, very few tools have been built for the JavaScript language, more specifically, there is a lack of mutation testing tools for the Node.js runtime and npm based applications. The npm Registry is a public collection of modules of open-source code for Node.js, front-end web applications, mobile applications, robots, routers, and countless other needs of the JavaScript community. The over 700,000 packages hosted in npm are downloaded more than 5 billion times per week. More and more software is published in npm every day, representing a huge opportunity to share code and solutions, but also to share bugs and faulty software. In this thesis, I describe prior work for mutation operators in JavaScript and Node.js, and propose Mutode, an open source tool which leverages the npm package ecosystem to perform mutation testing for JavaScript and Node.js applications. Finally, I empirically evaluated Mutode effectiveness by running it on the top 20 npm modules that have automated test suites